FUNCTIONAL AND MICROSTRUCTURAL PROPERTIES OF PLEUROTUS FLORIDA AND CALOCYBE INDICA FLOUR AND PROTEIN CONCENTRATE - T. R. Thirumuruga Ponbhagavathi1; S. Kanchana; C. Hemalatha; S. Vellaikumar; K. Kalpana (Journal of Animal and Plant Sciences, 2022)
Pleurotus florida(Oyster mushroom) and Calocybe indica(Milky Mushroom) are edible mushrooms commercially cultivated in India next to button mushroom has significant nutritional values and functional protein concentrates (PCs)and this can be obtained from nutrient dense powdered mushroom. Proximate composition and functional properties of flours and PCs derived from P.florida and C.indica were evaluated in this study. Fruiting bodies of mushroom were dried at 60-65°C in a cabinet drier and ground to produce flour.PCs were recovered from mushroom flours through isoelectric precipitation. Oyster mushroom (OM) and Milky Mushroom (MM) flour had protein content as 27.81% and 22.2% respectively. The protein content in the mushrooms increased to two-fold in PCs ie.from 27.81 to 50.47% in OM and 22.2 to 48.23% in MM.Flours were brighter contributing higher L* value than their corresponding concentrates, mainly due to pale yellow colour of mushroom flours and brownish colour of PCs.PCs presented significantly (p<0.05) higher Water Absorption Capacity, foaming capacity and emulsion capacity with lower bulk density and oil absorption capacity than their corresponding flours. Flours and protein concentrate had minimum gelation concentration of 6 and 8% for OM and MM respectively. The above results indicate that the flour and protein concentrates from P.florida and C.indica have remarkable functional properties, valuable in food industry with improved textural properties.
Keywords: Pleurotus florida; Calocybe indica; protein concentrates; functional properties; isoelctric precipitation